2020
DOI: 10.15694/mep.2020.000076.1
|View full text |Cite
|
Sign up to set email alerts
|

Transformation to learning from a distance

Abstract: COVID-19 is a strong disruptive force that has not only influenced our global health and economy but also has changed the way we teach, learn and communicate with our students. It has disturbed the regular education pattern and the standard practices that we adapted over many years. The challenge is beyond changing the mode of delivering instructions from face to face to online. The real challenge is in creating a culture that supports the adoption of innovative practices, which require different skills and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 15 publications
4
82
0
7
Order By: Relevance
“…The synchronous components of these were similar to those described above. The asynchronous components involved making recordings of previous lectures available and making additional learning resources available through curation or de novo creation (Taylor et al 2020;Veasuvalingam and Goodson 2020). In the papers that used asynchronous approaches, emphasis was placed on the need for organization and structure to support learning in the virtual environment.…”
Section: Pivoting Education Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The synchronous components of these were similar to those described above. The asynchronous components involved making recordings of previous lectures available and making additional learning resources available through curation or de novo creation (Taylor et al 2020;Veasuvalingam and Goodson 2020). In the papers that used asynchronous approaches, emphasis was placed on the need for organization and structure to support learning in the virtual environment.…”
Section: Pivoting Education Deliverymentioning
confidence: 99%
“…This section is a summary of the lessons learned and conclusions by the primary study authors, rather than the review authors views. Most authors described the introduced changes in positive terms, using statements such as 'overwhelmingly positive,' 'very positive,' 'high quality,' 'highly satisfied' in 7 studies ( Finn et al 2020; Khan 2020; Rose et al 2020), 'positive' or 'valuable' or 'useful' in 4 studies (Choi et al 2020;Gaber et al 2020;Lubarsky 2020;Taylor et al 2020), 'successful' or 'sufficient' or 'equivalent' in 7 studies (Buonsenso et al 2020;Burns and Wenger 2020;Christensen et al 2020;Hanel et al 2020;Rasmussen et al 2020;Torres et al 2020;Ungtrakul et al 2020). No study was reported by the authors as wholly unsuccessful or unfeasible, however, some developments were noted to be less desirable than in-person activities, most notably among activities replacing clinical placements (Chick et al 2020).…”
Section: Conclusion Of Study Authorsmentioning
confidence: 99%
“…A hybrid curriculum is what is needed with a clear distinction of the red ags for each experience (6). Distance learning is itself a form of blended learning, using a variety of coordinated and planned modalities and methods to deliver the curriculum and enable students to learn effectively (7).…”
Section: Resultsmentioning
confidence: 99%
“…In DL learners can be lost when there is too much emphasis on self-directed learning. This led experts to renown self-directed learning when describing best DL practices (7).…”
Section: Curriculum and Logistics Tensionmentioning
confidence: 99%
See 1 more Smart Citation